2021
DOI: 10.1002/admi.202101377
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Doping As Mechanism of Self‐Assembled Monolayers Functionalized Electrodes in Organic Field Effect Transistors

Abstract: Coating electrodes with self‐assembled monolayer (SAM) of polar molecules is known to reduce contact resistance (RC) in organic field effect transistors (OFETs). It is shown that the behavior of SAM in OFETs can be explained by considering a mechanism of interfacial doping in organic semiconductor by electrodes due to charge transfer during interface formation. The enhancement is analyzed in performance of pentacene OFETs with Cu electrodes, by coating Cu with SAM of pentafluorobenzenethiol or perfluorodecanet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, the above charge transport properties are highly related with the charge carrier properties in the NM/AM FET device [56–58] . Therefore, we calculate the reorganization energy ( λ ) for both the isolated NM/AM molecule and the NM/AM FET devices, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the above charge transport properties are highly related with the charge carrier properties in the NM/AM FET device [56–58] . Therefore, we calculate the reorganization energy ( λ ) for both the isolated NM/AM molecule and the NM/AM FET devices, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the above charge transport properties are highly related with the charge carrier properties in the NM/ AM FET device. [56][57][58] Therefore, we calculate the reorganization energy (λ) for both the isolated NM/AM molecule and the NM/ AM FET devices, respectively. The reorganization energy is defined as the energy required for the geometric relaxation during the charge transfer process, and it is inversely proportional to the mobility of charge carrier.…”
Section: Single-molecule Fetmentioning
confidence: 99%
“…The surface and interface properties of metal surfaces can be readily tuned by the formation of closely packed and highly ordered self-assembled monolayers (SAMs) derived from organic molecules with chemically active anchoring groups and various backbone structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Hence, SAMs provide a versatile tool for the preparation of functional molecular thin films that can be applied to many practical applications, such as surface passivation [ 16 ], biointerfaces [ 17 ], biosensors [ 18 ], molecular photodiodes [ 19 ], batteries [ 20 ], and molecular electronic devices [ 21 , 22 ]. Among many organic thiols, n -alkanethiols with various alkyl chains are the most popular precursors because they easily form closely packed and well-ordered SAMs on gold with a high reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that orbital interactions at the interface significantly contribute to governing charge transport at the interface. 12,13 Especially, hole injection involves an electron extraction from the highest occupied molecular orbital (HOMO) of the OSC by the electrode. Therefore, the HOMO energy level and distribution are anticipated to be critical in affecting the charge-transfer process.…”
Section: Introductionmentioning
confidence: 99%